Rwanda’s agrifood system: Structure and drivers of transformation - Diao, Xinshen; Ellis, Mia; Mugabo, Serge; Pauw, Karl; Rosenbach, Grace; Spielman, David J.; Thurlow, James (International Food Policy Research Institute, 2022)
This paper assesses the structure of Rwanda’s current and evolving agrifood system and its contribution to national development. The paper reiterates the point that Rwanda’s agrifood system stretches well beyond primary agriculture and creates jobs and income opportunities throughout the economy. While off-farm components of Rwanda’s agrifood system have generally grown more rapidly than primary agriculture in recent years, growth varies across value chains of the agrifood system in the studied period. The growth diagnostic in this paper reveals that it is domestic markets that have driven the recent growth in Rwanda’s AFS other than exports. The paper’s forward-looking analysis assesses potentially differential impacts of value-chain development efforts on broad development outcomes. The analysis measures the synergies and trade-offs of value-chain development in the context of an inclusive agricultural transformation. Such analysis is conducted using the Rwanda Computable General Equilibrium (CGE) model – an adaption of IFPRI’s Rural Investment and Policy Analysis (RIAPA) model to the Rwandan context. The modeling results indicate that value chains differ considerably in their effectiveness in achieving development goals and there are significant trade-offs among different development goals from promoting a specific value chain. The value chains that make a larger contribution to growth or job creation are not necessarily effective in reducing poverty or improving dietary quality – for example, value chains for coffee and tea – while value chains that play an important role in improving dietary quality may contribute less to job creation – such as vegetables or fruits. While there is no single value chain that can achieve all development goals effectively, it is possible to select a diversified set of value chains that complement each other in achieving different development goals. This latter strategy is a more realistic approach to growth and development.